Peran Orang Tua dalam Pemenuhan Kebutuhan Informasi Kesehatan Reproduksi pada Remaja - Agustin Mahardika Hariyadi (Yayasan Literasi Sains Indonesia, 2024)
Adolescents' problems with their reproductive organs receive less attention because they are relatively young, still in educational status and as if teenagers are free from the possibility of facing complications and diseases related to their reproductive organs. Adolescents who are looking for self-identity will very easily receive information related to problems with the function of their reproductive organs which tend to lead to sexual intercourse. This is due to a lack of parental participation, because they are busy earning a living so they don't pay enough attention to it, as well as a lack of parental knowledge related to their education. This research uses a descriptive quantitative design with questionnaires and online interviews with respondents. 35 teenagers aged 15-17 years who were in high school were the respondents in this study. The results of research from 35 children showed that 80% of parents played a role, 14.2% played a very important role, and 5.7% played a less important role. The conclusion of the research is that parents play a very important role in fulfilling the reproductive health information needs of adolescents. It is hoped that there will be outreach from health workers or collaboration with universities in the health sector to provide education to teenagers in high school regarding reproductive health.